2000
DOI: 10.1063/1.1305825
|View full text |Cite
|
Sign up to set email alerts
|

The role of kinetics in the nucleation and void formation in copper films produced by chemical vapor deposition

Abstract: Articles you may be interested inComparative study of the role of the nucleation stage on the final crystalline quality of (111) and (100) silicon carbide films deposited on silicon substrates.Correlation between the early stage of copper metal organic chemical vapor deposition and the material properties of thin filmThe heterogeneous nucleation and subsequent growth of chemical vapor deposited copper using hexafluoroacetylacetonate-Cu͑I͒-trimethylvinylsilane on physical vapor deposited tantalum and chemical v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 8 publications
0
11
0
Order By: Relevance
“…[8][9][10][11][12][13][14][15] Film thickness significantly influences the progress of agglomeration. 16 20 After the same heat-treatment, the film thickness is thinner, the agglomeration occurs easier.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…[8][9][10][11][12][13][14][15] Film thickness significantly influences the progress of agglomeration. 16 20 After the same heat-treatment, the film thickness is thinner, the agglomeration occurs easier.…”
Section: Resultsmentioning
confidence: 99%
“…1 2 In order to overcome the disadvantages of Cu such as fast diffusion into Si 3 and SiO 2 , 4 and poor adhesion to most dielectric materials, a suitable diffusion barrier/adhesion promoter is necessary. [5][6][7][8][9][10][11][12][13][14][15] However, it is observed that after high temperature annealing, copper films on some barriers may exhibit agglomeration, such as MoN, 8 TiN, 9 Ti-Si-N, 10 TiB 2 , 11 12 WC, 13 Ta, 14 ITO. 15 With the annealing temperature increasing, Cu films systems exhibit grain growth, void formation, agglomeration and chemical reaction with the Si substrate (formation of Cu 3 Si).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For 45 nm generation, deposition of a thin alloy seed layer should be deposited by conformal deposition methods such as Chemical Vapor Deposition (CVD), Atomic Layer Deposition (ALD), or Supercritical Fluid (CO 2 ) Deposition (SCFD) in which the process temperature is high enough for surface diffusion of Cu [23 -27]. To apply a Cu(Sn) alloy as the seed layer for electroplating or for filling a deep sub-micron trench, the effect of alloy elements on the morphology of Cu thin film is important for seamless and void-free deposition [23,24].…”
Section: Introductionmentioning
confidence: 99%
“…Nucleation studies to date have shown poor wetting of Cu nuclei on air exposed TiN, where film growth proceeds via the Volmer-Weber ͑island͒ growth mode. 6,9,10 Yoen, Park, and Rhee 11 reported maximum nuclei densities (N max ) of approximately 1.7 and 2.3 ϫ10 9 cm Ϫ2 on sputtered TiN for Cu CVD at a limited set of substrate temperatures (T s ): 180 and 220°C.…”
mentioning
confidence: 99%